AS "Laima" finanšu analīze - Šikova, Jekaterina (Latvijas Universitāte, 2009)
Diplomdarba nosaukums: „A/S „Laima” finanšu analīze”. Diplomdarba mērķis: balstoties uz finanšu stāvokļa analīzi laika periodā no 2005.līdz 2007.gadam, uzņēmumā „Laima” noteikt galvenās attīstības problēmas un tendences, kā arī izstrādāt ieteikumus tālākai darbības uzlabošanai. Diplomdarba apjoms ir 63 lpp., t.sk. 3 nodaļas: Pirmajā daļā apskatīti finanšu analīzes teorētiskie aspekti. Otrajā - veikta A/S „Laima” finanšu analīze par 2005.-2007.g., novērtējot uzņēmuma finanšu rādītāju tendences, analizējot bilances struktūras izmaiņas, cēloņus un tendences. Trešajā daļā autores rekomendācijas uzņēmuma finansiālās situācijas uzlabošanai. Ir secinājumi un priekšlikumi, 4 pielikumi, izmantotas 11 tabulas un 28 formulas. Bilances horizontālā un vertikālā analīze, likviditāte, rentabilitāte, aktivitāte, maksātspēja, bankrota diagnostika.

The title of this bachelor paper is „The financial analysis of the JSC Laima”. The purpose of this bachelor paper is to define the main challenges and issues that this specific company is facing, based on the analysis of the financial situation from 2005 until 2007, as well as to develop recommendations for improvement of the further actions. The dimension of this graduation paper is 63 pages, including 3 chapters. The first chapter deals with the theoretical facets of the financial analysis. Whilst the second chapter covers the JSC Laima financial analysis from 2005 to 2007, evaluating the tendencies of the company’s financial directory, analyzing the changes in the structure of the balance, causes and issues. The third chapter presents authors recommendations to improve the financial situation. In the bachelor work conclusions and proposals are drawn, there are four attachments, 11 charts and 28 formulas used. The horizontal and vertical analysis of the balance, liquidity, profitableness, activity, paying capacity, bankruptcy diagnostics.
Financial analysis of JSC "Laima'
Keywords: Ekonomika